2009
DOI: 10.1245/s10434-009-0579-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Vascular Endothelial Growth Factor in Squamous Cell Carcinomas of the Tonsil in Relation to Human Papillomavirus Status and Epidermal Growth Factor Receptor

Abstract: HPV is a stronger prognostic marker than VEGF or EGFR in tonsillar SCCs. VEGF correlates with MVD in these tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
3
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 33 publications
0
29
3
1
Order By: Relevance
“…Therefore, assuming EGFR were truly under-expressed in HPV-positive HNSCC, one might expect a reduction in VEGF expression in HPV-positive tumors. However, our study and one other [10] showed no difference in VEGF expression comparing HPV-positive and HPV-negative HNSCC. While this result might be attributable to low statistical power, it is curious that we made this observation in the same sample that showed higher EGFR expression in HPV-negative HNSCC.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…Therefore, assuming EGFR were truly under-expressed in HPV-positive HNSCC, one might expect a reduction in VEGF expression in HPV-positive tumors. However, our study and one other [10] showed no difference in VEGF expression comparing HPV-positive and HPV-negative HNSCC. While this result might be attributable to low statistical power, it is curious that we made this observation in the same sample that showed higher EGFR expression in HPV-negative HNSCC.…”
Section: Discussioncontrasting
confidence: 86%
“…Only two studies reported on VEGF expression in HNSCC according to tumor HPV status and one study showed an association whereas the other did not [10,17]. Few IHC studies have examined the EGFR-VEGF association in HNSCC, with one study reporting a positive association in a heterogeneous HNSCC case series [18], and two studies showing a null association in tonsil [10] and oral cavity cancer [19]. We are unaware of any studies examining the EGFR-VEGF association by tumor HPV status in HNSCC.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The relationship of HPV status with EGFR protein expression and clinical outcome has been reported in several small series (10,11,18,19,21,26), indicating that best outcomes are observed in patients with HPV-positive tumors with low EGFR expression. An inverse relationship between HPV status and EGFR gene amplification has been reported (27,28); however, to date the relationship between HPV status, EGFR gene copy number, and clinical outcome in HNSCC has not been examined.…”
Section: Introductionmentioning
confidence: 87%
“…The latter results have been conWrmed by Brocic et al, who also rejected VEGF as a clinical parameter for prognosis and outcome [10]. Fei et al [30] analyzed 85 SCC of the tonsil and could not reveal any associations between VEGF and HPV status, gender, patient age, TNM stage or EGFR expression either.…”
Section: Angiogenesismentioning
confidence: 91%